SURFACE MODIFICATION OF TITANIUM ALLOY FOR BIOCOMPATIBILITY - Omarov, Salikh (School of Engineering and Digital Sciences, 2023)
Despite the research development in biomedicine, orthopedical implant application is still facing several challenges. The relatively vast number of implant failures in long-term applications motivates the current research to reduce their possibilities to occur. One of the vital aspects in achieving that is modification of implant surfaces. So far, many surface modification techniques have been investigated, however, electro discharge machining (EDM) is a promising technique in surface treatment of conductive materials such as titanium alloys. Moreover, printing implants with selective laser melting (SLM) is gaining bigger attention due to the flexibility of production of complex bone-like shapes. The thesis work is focused on modification of mechanical properties as well as biocompatibility of machined surfaces of both casted and printed biomedical Ti-6Al-4V titanium alloys by EDM through altering surface characteristics. Machining performance such as material removal rate (MRR), overcut and kerf width and surface aspects such as surface roughness, crater sizes, hardness, surface free energy and biofilm formation of pseudomonas aeruginosa bacteria are observed. Based on these results, the effects of parameter values of gap voltage, pulse current, time on and duty factor of drilling EDM as well as parameter values of capacitance and voltage of micro EDM were observed. Comparing casted and printed titanium alloys, modifications of surfaces on printed titanium alloy have better performance in MRR, kerf width, crater size and surface roughness, meanwhile, casted titanium alloy has better performance in contact angle and hardness values. Moreover, despite high overall resistance on bacteria adhesion and biofilm formation, biological analysis showed that these results correlate with discharge energy of EDM process. Low discharge energy resulted in a bigger number of bacterial strains while high energy had better resistance to bacteria. Therefore, by analyzing the effect of EDM on modified surface, it was observed that the resistance to bacteria adhesion and biofilm formation increased for higher discharge energy while comparison between casted and printed titanium alloy showed that printed titanium alloy has better performance in EDM treatment for biocompatibility purposes.
Keywords: type of access: open access; lectro discharge machining; titanium alloys; biomedical implant material; selective laser melting; Ti-6Al-4V; biofilm formation; bacteria adhesion